High-strength UV adhesive tape and preparation method thereof
By adopting a composite substrate layer structure and an adhesive layer of the introduced end thiol nitrile rubber and epoxy resin, the problem that existing high-strength tape is difficult to maintain good bonding properties while improving mechanical strength and aging resistance, and achieving high-strength, high toughness and good bonding properties.
Patent Information
- Application Number
- CN202411847713.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
AI Technical Summary
While improving mechanical strength and aging resistance, existing high-strength tapes are difficult to maintain good bonding properties, and the process is complicated, resulting in insufficient shear strength and poor bonding properties.
The composite substrate layer structure is adopted, including the first substrate layer, the adhesive layer and the second substrate layer. End thiol nitrile rubber and epoxy resin are introduced into the adhesive layer to form micron-scale rubber particles to improve the strength and toughness of the adhesive layer, and an adhesive layer is provided on both sides of the composite substrate layer to enhance the bonding properties.
The balance between high strength, high toughness and good bonding properties of the tape is achieved, the shear strength and impact resistance are improved, and the process flow is simplified.
Smart Images

Figure CN119614090A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, and in particular to a high-strength UV adhesive tape and a preparation method thereof. Background Art
[0002] High-strength tapes have higher strength and thickness than ordinary tapes, and are often used in the following scenarios: packaging and transportation of heavy items such as machinery and equipment, metal plates, etc.; bonding of automotive accessories, dashboards, battery cells, etc.; fixing of electronic components, etc. Traditionally, such tapes are generally made of foam tapes, cloth-based tapes, etc. Although such tapes have high adhesion, their overall strength needs to be improved.
[0003] There are also methods to increase the strength by increasing the thickness of the tape. The common practice is to thicken the substrate or stack the adhesive film. However, thickening the substrate will result in insufficient shear strength of the tape, making it difficult to meet the requirements of structural bonding. The stacking of multiple layers of adhesive film is not only cumbersome in process, but also has problems such as poor adhesion and poor strength.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The invention provides a high-strength UV adhesive tape, which can achieve a balance among the mechanical strength, aging resistance and conformability of the adhesive tape.
[0006] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a high-strength UV tape, comprising a composite substrate layer and an adhesive layer arranged on at least one side of the composite substrate layer, wherein the composite substrate layer comprises a first substrate layer, an adhesive layer and a second substrate layer in sequence, and the adhesive layer is arranged on the first substrate layer and / or the second substrate layer away from the adhesive layer;
[0007] The adhesive layer comprises the following components in parts by weight:
[0008]
[0009]
[0010] Furthermore, the mass ratio of the first epoxy resin to the mercapto-terminated nitrile rubber is (3-20):1.
[0011] Furthermore, the first epoxy resin comprises a combination of a solid epoxy resin having an epoxy equivalent of 420 to 800 g / eq and a liquid epoxy resin having an epoxy equivalent of 180 to 250 g / eq.
[0012] Furthermore, the mass ratio of the solid epoxy resin to the liquid epoxy resin is (1-5):1.
[0013] Furthermore, the first substrate layer and the second substrate layer are both PET films.
[0014] Furthermore, the thickness of the first substrate layer and the second substrate layer are both ≤38 μm. Furthermore, the thickness of the first substrate layer and the second substrate layer are each independently selected from 25 to 38 μm.
[0015] Furthermore, the thickness of the adhesive layer is 50-150 μm.
[0016] Furthermore, adhesive layers are provided on both sides of the composite substrate layer.
[0017] Furthermore, the thickness of the adhesive layer is 50 to 150 μm.
[0018] The second aspect of the present invention provides a method for preparing the high-strength UV tape described in the first aspect of the present invention, comprising the following steps: mixing and stirring the components of the adhesive layer evenly, coating the components on the surface of the first substrate layer, and then bonding the second substrate layer to cure and dry to obtain a composite substrate layer; coating the adhesive of the adhesive layer on at least one side of the composite substrate layer, and obtaining an adhesive layer after curing and drying.
[0019] Furthermore, the method further comprises the following step: laminating a release film on the surface of the dried adhesive layer.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention uses a composite structure of a first substrate layer-adhesive layer-second substrate layer as a composite substrate. Compared with simply increasing the thickness of the substrate layer, this structural design not only improves the strength of the tape, but also enables the tape to have higher toughness to maintain the adhesiveness of the tape;
[0022] (2) In the adhesive layer of the present invention, the terminated mercapto-nitrile rubber and the epoxy resin are introduced into the acrylic ester copolymer. Since the terminated mercapto-nitrile rubber forms micron-sized rubber particles in the epoxy resin, the strength of the adhesive layer can be improved. In addition, during the curing process, the terminated mercapto-nitrile rubber and the epoxy resin form a phase separation structure. The rubber particles can absorb strain energy and thus improve the toughness of the adhesive layer. As a result, the adhesive tape prepared from the composite substrate of the present invention has a balance between high strength, high toughness and conformability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a tape adhesion test diagram corresponding to Example 6a of the present invention;
[0025] Figure 2 This is a tape adhesion test diagram corresponding to Example 6c of the present invention;
[0026] Figure 3 This is a tape adhesion test diagram corresponding to Example 6d of the present invention. DETAILED DESCRIPTION
[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0029] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0030] The types of substrates used in existing high-strength tapes include polyethylene terephthalate (PET) film, foam and cloth base, etc. Foam and cloth base have low strength themselves, and can improve cushioning and bonding properties, but are not suitable for some scenarios that require wear resistance; PET film has strong rigidity and high stiffness, but if the thickness of PET is increased to improve strength, its conformability will significantly deteriorate.
[0031] Based on this, the first aspect of the present invention provides a high-strength UV tape, comprising a composite substrate layer and an adhesive layer disposed on at least one side of the composite substrate layer, wherein the composite substrate layer sequentially comprises a first substrate layer, an adhesive layer and a second substrate layer, and the adhesive layer is disposed on the first substrate layer and / or the second substrate layer away from the adhesive layer;
[0032] The adhesive layer comprises the following components in parts by weight:
[0033]
[0034] The adhesive tape of the present invention adopts the composite structure of the first substrate layer-adhesive layer-second substrate layer as the composite substrate, which not only increases the strength of the substrate layer, but also takes into account the conformability; by introducing the terminal mercapto nitrile rubber and the epoxy resin into the acrylate copolymer in the adhesive layer, the active group of the terminal mercapto nitrile rubber reacts chemically with the epoxy group or hydroxyl group of the epoxy resin to form a stable chemical bond, which not only enhances the interaction force between the terminal mercapto nitrile rubber and the epoxy resin, but also promotes the mutual interweaving and entanglement of the molecular chains of the two, thereby constructing a more compact and tough blending system, and chemical crosslinking makes the interface between the terminal mercapto nitrile rubber and the epoxy resin more firmly, reducing interface defects and stress concentration phenomena. When the material is subjected to external force, it can more effectively transfer and disperse stress, prevent the initiation and expansion of cracks, and thus enhance fracture toughness. The adhesive tape composed of the composite substrate of the present invention takes into account high strength and high toughness, which is conducive to improving the conformability of the adhesive tape.
[0035] For example, in different embodiments, the amounts of the components in the adhesive layer may be as follows, measured by weight:
[0036] The amount of the first acrylate copolymer can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two ends thereof; by adjusting the amount of the first acrylate copolymer within the above range, the adhesive layer can have excellent bonding strength;
[0037] The amount of the first epoxy resin can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two ends thereof;
[0038] The amount of the mercapto-terminated nitrile rubber can be 1.5 parts, 2.5 parts, 5 parts, 8 parts, 10 parts, 16 parts, 20 parts or any value between any two end values; the introduction of the first epoxy resin and the mercapto-terminated nitrile rubber in appropriate amounts helps to improve both the rigidity and toughness of the adhesive layer;
[0039] The dosage of the first cationic photoinitiator can be 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two ends thereof; by introducing the first cationic photoinitiator, polymerization is initiated under light irradiation to achieve curing.
[0040] In a specific embodiment of the present invention, the mass ratio of the first epoxy resin to the terminal mercapto nitrile rubber is (3-20) : 1, specifically 3: 1, 5: 1, 8: 1, 10: 1, 15: 1, 18: 1, 20: 1 or any value between any two end values. The inventors of the present invention have found that regulating the mass ratio of the first epoxy resin to the terminal mercapto nitrile rubber within a limited range is beneficial to improving both the strength and toughness of the substrate. When the ratio of the first epoxy resin to the terminal mercapto nitrile rubber is greater than 20: 1, the toughening effect of the terminal mercapto nitrile rubber is not obvious; when the ratio is less than 3: 1, although the toughness can be improved, the excessive terminal mercapto nitrile rubber will destroy the rigid structure of the epoxy resin, resulting in a decrease in overall strength.
[0041] In a specific embodiment of the present invention, the first epoxy resin comprises a combination of a solid epoxy resin having an epoxy equivalent of 420 to 800 g / eq and a liquid epoxy resin having an epoxy equivalent of 180 to 250 g / eq. For example, in different embodiments, the epoxy equivalent of the solid epoxy resin may be 420 g / eq, 450 g / eq, 500 g / eq, 550 g / eq, 600 g / eq, 650 g / eq, 700 g / eq, 750 g / eq, 800 g / eq, or any value between any two end values; the epoxy equivalent of the liquid epoxy resin may be 180 g / eq, 200 g / eq, 220 g / eq, 230 g / eq, 250 g / eq, or any value between any two end values. The "epoxy equivalent" in the present invention refers to the number of grams of epoxy resin containing one equivalent of epoxy groups. The higher the value, the less epoxy groups therein. The inventors of the present invention have found that when a combination of two epoxy resins in different forms is used in the system, the resulting adhesive tape has better bonding properties.
[0042] Furthermore, the mass ratio of the solid epoxy resin to the liquid epoxy resin is (1-5) : 1. The mass ratio of the solid epoxy resin to the liquid epoxy resin can be 1:1, 2:1, 3:1, 4:1, 5:1 or any value between any two end values. Liquid epoxy resin has good fluidity, while solid epoxy resin has good mechanical properties. When the mass ratio of the two resins is limited to the above range in the present invention, the formed tape has good bonding performance.
[0043] In a specific embodiment of the present invention, the solid epoxy resin includes at least one of epoxy resin E-12, epoxy resin E-20 and epoxy resin E-21; the liquid epoxy resin includes at least one of epoxy resin E-44 and epoxy resin E-51.
[0044] In a specific embodiment of the present invention, both the first substrate layer and the second substrate layer are PET films.
[0045] In a specific embodiment of the present invention, the thickness of the first substrate layer and the second substrate layer does not exceed 38 μm, preferably 25 to 38 μm. For example, in different embodiments, the thickness of the first substrate layer and the second substrate layer are independently selected from 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm or any value between any two end values. The thickness of the first substrate layer may be the same as or different from the thickness of the second substrate layer. By regulating the thickness of the first substrate layer and the second substrate layer within the above range, the balance between the strength and toughness of the composite substrate layer can be taken into account.
[0046] In a specific embodiment of the present invention, the thickness of the adhesive layer is 50-150 μm. For example, in different embodiments, the thickness of the adhesive layer is 50 μm, 75 μm, 100 μm, 125 μm, 150 μm or any value between any two ends thereof.
[0047] In a specific embodiment of the present invention, the first cationic photoinitiator can be a conventional commercially available cationic photoinitiator, such as at least one of photoinitiator 1176, photoinitiator 261, photoinitiator 262, photoinitiator 1172 and photoinitiator 548, so as to be able to initiate cationic polymerization of the components in the adhesive layer under light irradiation to achieve curing.
[0048] The solid content of the first acrylate copolymer of the present invention is 20% to 40%, specifically 20%, 25%, 30%, 35%, 40% or any value between the two ends thereof. The solid content of the first acrylate copolymer can be adjusted according to actual needs and is not limited to the above limited range.
[0049] The invention provides a self-made acrylic ester copolymer and a preparation method thereof. The first acrylic ester copolymer is mainly prepared by copolymerization of acrylic ester monomers; the acrylic ester monomers include 15 to 35 parts by weight of soft monomers, 40 to 60 parts by weight of hard monomers and 5 to 20 parts by weight of functional monomers.
[0050] For example, in different embodiments, the content of the soft monomer can be 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, or any value between any two ends thereof; the content of the hard monomer can be 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, or any value between any two ends thereof; the content of the functional monomer can be 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, or any value between any two ends thereof. By adjusting the ratio of each monomer within the above range, it is more conducive to improving the bonding strength of the adhesive layer.
[0051] In a specific embodiment of the present invention, the soft monomer includes at least one of isooctyl acrylate, ethyl acrylate and butyl acrylate.
[0052] In a specific embodiment of the present invention, the hard monomer includes at least one of methyl acrylate and methyl methacrylate.
[0053] In a specific embodiment of the present invention, the functional monomer includes at least one of glycidyl methacrylate, hydroxyethyl acrylate and hydroxypropyl acrylate.
[0054] In a specific embodiment of the present invention, the first acrylate copolymer further includes 0.1 to 1 parts by weight of a thermal initiator. The content of the thermal initiator can be specifically 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 part by weight, or any value between any two end values. The thermal initiator can be a conventional azo initiator, an organic peroxide thermal initiator, etc. The azo initiator includes but is not limited to at least one of azobisisobutyronitrile and azobisisoheptonitrile. When the thermal initiator changes, the reaction temperature for the preparation of the acrylate copolymer can be appropriately adjusted to be able to initiate the polymerization of the monomers.
[0055] In a specific embodiment of the present invention, the first acrylate copolymer further comprises 100 to 300 parts by weight of a solvent. The content of the solvent may be 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, or any value between the two end values. The solvent may be a conventional solvent, including but not limited to at least one of ethyl acetate, toluene, ethanol, and acetone.
[0056] In a specific embodiment of the present invention, the preparation of the first acrylate copolymer includes: weighing raw materials in proportion, reacting at 50-70°C for 6-12 hours under a protective atmosphere. The protective atmosphere may be nitrogen, but is not limited thereto; the reaction temperature may be 50°C, 55°C, 60°C, 65°C, 70°C or any value between any two ends thereof; and the reaction time may be 6 hours, 8 hours, 10 hours, 12 hours or any value between any two ends thereof.
[0057] In a specific embodiment of the present invention, the adhesive layer can be provided on one side or both sides of the composite substrate layer to form a single-sided tape or a double-sided tape, respectively. The type of the specific tape can be conventionally adjusted according to actual needs.
[0058] In a specific embodiment of the present invention, the thickness of the adhesive layer is 50 to 150 μm. For example, in different embodiments, the thickness of the adhesive layer can be 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm or any value between any two end values. For example, adhesive layers are provided on both sides of the composite substrate layer, namely the first adhesive layer and the second adhesive layer, and the first adhesive layer is provided on one side of the first substrate layer, and the second adhesive layer is provided on one side of the second substrate layer. The thickness of the first adhesive layer and the second adhesive layer can be the same or different, as long as they meet the above range interval.
[0059] In a specific embodiment of the present invention, the adhesive layer comprises the following components in parts by weight:
[0060]
[0061] The adhesive layer of the present invention is a delayed curing adhesive, which has multiple excellent properties of traditional pressure-sensitive adhesives before ultraviolet light irradiation, such as high peeling force and easy lamination, and produces excellent bonding strength after curing after ultraviolet light irradiation.
[0062] For example, in different embodiments, the amounts of the components in the adhesive layer of the present invention may be as follows, in parts by weight:
[0063] The amount of the second acrylate copolymer can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two ends thereof;
[0064] The amount of the second epoxy resin can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two ends thereof;
[0065] The amount of the hyperbranched polyester polyol can be 2 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts or any value between any two ends thereof;
[0066] The amount of the second cationic photoinitiator can be 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two ends thereof;
[0067] The amount of the silane coupling agent can be 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two ends thereof.
[0068] In a specific embodiment of the present invention, the types of the second acrylate copolymer, the second epoxy resin and the second cationic photoinitiator in the adhesive layer can be selected from the specific types of the first acrylate copolymer, the first epoxy resin and the first cationic photoinitiator in the adhesive layer mentioned above, which will not be repeated here.
[0069] In a specific embodiment of the present invention, the hyperbranched polyester polyol can be commercially available hyperbranched polyester polyol, including but not limited to Boltorn produced by Perstorp of Sweden. TM H2004, Boltorn TM H311, Boltorn TM U3000, Boltorn TM P500 and Boltorn TM At least one of P1000.
[0070] In a specific embodiment of the present invention, the silane coupling agent may be a conventional silane coupling agent, which is not specifically limited in the present invention. For example, the silane coupling agent may be at least one of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-570.
[0071] The second aspect of the present invention also provides a method for preparing the high-strength UV tape described in the first aspect of the present invention, comprising the following steps: mixing and stirring the components of the adhesive layer evenly, coating the components on the surface of the first substrate layer, and then bonding the second substrate to cure and dry to obtain a composite substrate layer; coating the adhesive of the adhesive layer on at least one side of the composite substrate layer, and obtaining an adhesive layer after curing and drying.
[0072] The coating method is not limited, and roller coating, blade coating or dip coating etc. can be adopted. In actual operation, coating can be carried out by a coater.
[0073] In a specific embodiment, the following steps are also included: a release film is attached to the surface of the adhesive layer; if the adhesive layer is provided on both sides of the composite substrate layer, then the release film can be provided on the sides of the first adhesive layer and the second adhesive layer, or the release film can be attached to the surface of only one of the adhesive layers, which can be provided according to actual needs. Among them, the release film may include materials such as PET film, polyimide (PI) film, polyethylene (PE) film, oriented stretch polypropylene (OPP) film, composite release film, etc. Since the release film will be peeled off during actual use, the thickness of the release film has little effect on the actual use of the product. The thickness of the release film can be freely selected according to actual needs, without special restrictions, for example, it can be 25 to 100 μm, specifically 25 μm, 40 μm, 60 μm, 80 μm, 100 μm or any value between the two ends.
[0074] The following specific examples are given to further illustrate the purpose and advantages of the present invention, but these examples should not be considered as limiting the present invention. In the following examples, 1 g represents 1 part by weight.
[0075] The composition and preparation method of the first acrylate copolymer and the second acrylate copolymer used in the following embodiments are the same, and the specific reference is as follows, but not limited thereto. The specific preparation method is: 50g of methyl acrylate, 25g of butyl acrylate, 10g of isooctyl acrylate, 8g of glycidyl methacrylate and 250g of ethyl acetate are placed in a reaction container, mixed evenly at 70°C under nitrogen protection, and then 0.5g of azobisisobutyronitrile is added and kept warm for 8h to obtain an acrylate copolymer, which is used for the preparation of the adhesive tape in the following embodiments.
[0076] Example 1
[0077] The present embodiment provides a high-strength UV tape, comprising a first release film layer, a first adhesive layer, a first substrate layer, an adhesive layer, a second substrate layer, a second adhesive layer, and a second release film layer arranged in sequence.
[0078] The raw materials of the first adhesive layer and the second adhesive layer include the following components by weight: 50g of acrylate copolymer, 30g of epoxy resin E-21, 20g of epoxy resin E-44, 1g of KH-560, and Boltorn TM H2004 2g, photoinitiator 1172 1g.
[0079] The raw materials of the adhesive layer include the following components by weight: 50 g of acrylate copolymer, 30 g of epoxy resin E-21, 20 g of epoxy resin E-44, 8 g of mercapto-terminated nitrile rubber (manufacturer: Goodrich Chemical Co., USA, model: Hycar-MTBN), and 1 g of photoinitiator 548.
[0080] The preparation method thereof comprises the following steps:
[0081] (1) Weigh each component according to the raw material ratio of the adhesive layer, stir evenly for 60 minutes under light-proof conditions, let it stand for 10 minutes to defoam, and then apply it on the surface of a 25 μm PET film. After the coating is completed, another 25 μm PET film is attached to the coated side, and then cured by mercury lamp radiation (light intensity 200 mj / cm 2 ) to obtain a composite substrate, wherein the thickness of the adhesive layer after curing is 100 μm;
[0082] (2) Weigh each component according to the raw material ratio of the first adhesive layer and the second adhesive layer, stir evenly for 60 minutes under light-proof conditions, let stand for defoaming for 10 minutes, and then apply it to both sides of the composite substrate obtained in step (1), bake at 90° C. for 5 minutes to form a first adhesive layer of 75 μm and a second adhesive layer of 75 μm, respectively, and cover the surfaces of the first adhesive layer and the second adhesive layer with PET release films, respectively. After curing at room temperature for 3 days, a high-strength UV tape is obtained.
[0083] Example 2
[0084] This example is carried out with reference to Example 1, the only difference being that the raw material ratio of the adhesive layer is different, and the preparation method and other components are the same as those of Example 1, and the specific differences are as follows:
[0085] The raw materials of the adhesive layer of this embodiment include the following components in parts by weight: 40 g of acrylate copolymer, 36 g of E-21 epoxy resin, 24 g of E-44 epoxy resin, 9.6 g of mercapto-terminated nitrile rubber, and 55 g of photoinitiator 548.
[0086] Example 3
[0087] This example is carried out with reference to Example 1, the only difference being that the raw material ratio of the adhesive layer is different, and the preparation method and other components are the same as those of Example 1, and the specific differences are as follows:
[0088] The raw materials of the adhesive layer of this embodiment include the following components in parts by weight: 60 g of acrylate copolymer, 18 g of E-21 epoxy resin, 12 g of E-44 epoxy resin, 4.8 g of mercapto-terminated nitrile rubber, and 0.5 g of photoinitiator 548.
[0089] Example 4 Group
[0090] This embodiment group was carried out with reference to the embodiment 1, and the only difference was that: the raw material ratio of the adhesive layer was different, specifically, the mass ratio of the epoxy resin to the mercapto-terminated nitrile rubber was adjusted by adjusting the amount of the mercapto-terminated nitrile rubber in the adhesive layer, and the preparation method and other components were the same as those in the embodiment 1, and the specific differences were as follows:
[0091] Example 4a: 16.67 g of mercapto-terminated nitrile rubber, the mass ratio of epoxy resin to mercapto-terminated nitrile rubber is 3:1;
[0092] Example 4b: 2.5 g of mercapto-terminated nitrile rubber, the mass ratio of epoxy resin to mercapto-terminated nitrile rubber is 20:1;
[0093] Example 4c: 20 g of mercapto-terminated nitrile rubber, the mass ratio of epoxy resin to mercapto-terminated nitrile rubber is 2.5:1;
[0094] Example 4d: 2 g of mercapto-terminated nitrile rubber, the mass ratio of epoxy resin to mercapto-terminated nitrile rubber is 25:1.
[0095] Example 5 Group
[0096] This embodiment group was carried out with reference to embodiment 1, except that the raw material ratio of the bonding layer was different, specifically, the masses of the two epoxy resins in the bonding layer were different. The preparation method and other components were the same as those in embodiment 1, and the specific differences were as follows:
[0097] Example 5a: 25 g E-21, 25 g E-44, the mass ratio of E-21 to E-44 is 1:1;
[0098] Example 5b: 41.67 g E-21, 8.33 g E-44, the mass ratio of E-21 to E-44 is 5:1;
[0099] Example 5c: 20 g E-21, 30 g E-44, the mass ratio of E-21 to E-44 is 0.67:1;
[0100] Example 5d: 42.86 g E-21, 7.14 g E-44, the mass ratio of E-21 to E-44 is 6:1;
[0101] Example 5e: 50 g E-21, without E-44;
[0102] Example 5f: No E-21, 50 g E-44.
[0103] Example 6 Group
[0104] This embodiment group was carried out with reference to the embodiment 1, except that: the composite substrate used the first substrate, the second substrate and the adhesive layer with different thicknesses, the total thickness of the composite substrate remained unchanged, and the preparation method and components were the same as those of the embodiment 1, and the specific differences were as follows:
[0105] Embodiment 6a: The thickness of the first substrate and the second substrate are both 38 μm, and the thickness of the adhesive layer is 74 μm;
[0106] Embodiment 6b: The thickness of the first substrate and the second substrate are both 20 μm, and the thickness of the adhesive layer is 110 μm;
[0107] Embodiment 6c: The thickness of the first substrate and the second substrate is 50 μm, and the thickness of the adhesive layer is 50 μm;
[0108] Example 6d: No adhesive layer is included, and 150 μm thick PET is directly used as the substrate.
[0109] Comparative Example 1
[0110] Comparative Example 1 was carried out with reference to Example 1, except that the raw material ratio of the adhesive layer was different, and its preparation method and other components were the same as those of Example 1. The specific differences are as follows:
[0111] Comparative Example 1a: The adhesive layer does not contain terminal mercapto-butadiene nitrile rubber;
[0112] Comparative Example 1b: An equal amount of hydroxy-terminated nitrile rubber (manufacturer: Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd., model: HTBN-A) was used in the adhesive layer instead of the mercapto-terminated nitrile rubber.
[0113] Test Case
[0114] In order to compare and illustrate the performance differences of the adhesive tapes of different embodiments and comparative examples, the following tests were performed on the adhesive tape samples prepared in each embodiment and comparative example. The test results are shown in Table 1, and the test methods are referenced as follows.
[0115] 180° peel strength test: The test was conducted according to the national standard GB / T 2792-2014 "Test method for peel strength of adhesive tape". The details are as follows: a three-series aluminum plate was used as the adhered object. Before the test, the three-series aluminum plate was wiped with ethanol three times, the release film on one side of the tape was peeled off, and 50μm etched PET was used to reinforce it and cut it into 150mm×25mm specifications; then the release film on the other side was peeled off, and the tape was irradiated with UV (mercury lamp, 200mJ / cm 2 ) to stimulate curing, immediately after irradiation, stick it on an aluminum plate, roll it twice with a 2kg roller, place the test sample in a controlled environment (23°C / 50% RH) for 2 days for post-curing, and then perform a 180° peel force test. For the application scenario of the present invention, the peel force of the tape must be ≥1N / mm.
[0116] Shear strength test: According to the national standard GB / T 7124-2008 "Determination of tensile shear strength of adhesives", the test uses a three-series aluminum plate as the object to be adhered; wipe the three-series aluminum plate with ethanol three times before the test; cut the double-sided tape with release film on both sides into 25mm×5mm specifications, peel off the release film on one side and stick it on the three-series aluminum plate, then peel off the release film on the other side, and irradiate the film with UV (mercury lamp, 200mJ / cm 2 ) to stimulate the curing process, and immediately after irradiation, stick it against another aluminum plate and press it with a force of 2kg for 30s. After that, place the test sample in a controlled environment (23℃ / 50%RH) for 2 days for post-curing, and then perform a shear strength test. For the application scenario of the present invention, the shear strength of the tape needs to be ≥7MPa.
[0117] Impact strength test: The test was conducted according to the national standard GB / T 8809-2015 "Test method for pendulum impact of plastic film", and the plate used was three-series aluminum. Before the test, the three-series aluminum plate was wiped with ethanol three times; the tape was cut into 10mm×10mm specifications, and the release film on one side was peeled off and pasted on a three-series aluminum block (10mm×10mm×3mm), and then the other layer of release film was peeled off, and the film was irradiated with UV (mercury lamp, 200mJ / cm 2 ) to stimulate the curing process, and immediately after irradiation, stick it to the center of another aluminum block (25mm×25mm×3mm) and press it with a force of 2kg for 30s. Then, place the test specimen in a controlled environment (23℃ / 50%RH) for 2 days for post-curing, and then perform an impact strength test. For the application scenario of the present invention, the impact strength of the tape must be ≥0.5J.
[0118] Table 1 Test results of different embodiments and comparative examples
[0119] serial number Peel force / N / mm Shear strength / MPa Impact strength / J Example 1 2.78 11.17 1.47 Example 2 1.08 10.76 0.68 Example 3 1.99 7.07 0.59 Example 4a 2.46 7.98 1.35 Example 4b 1.89 10.99 0.71 Example 4c 2.51 3.11 0.44 Example 4d 1.71 10.23 0.31 Example 5a 2.11 9.01 1.23 Example 5b 1.02 7.12 0.81 Example 5c 2.66 6.89 1.39 Example 5d 0.51 5.96 0.76 Example 5e 0.21 5.76 0.21 Example 5f 1.79 4.44 0.97 Example 6a 2.11 11.12 1.32 Example 6b 2.69 10.34 1.4 Example 6c 1.95 11.02 1.28 Example 6d 1.76 10.31 1.04 Comparative Example 1a 1.92 13.12 0.41 Comparative Example 1b 2.55 6.21 1.37
[0120] It can be seen from the above test results that the present invention adopts a composite structure of a first substrate layer-adhesive layer-second substrate layer as the substrate layer, which can ensure that the tape has a certain strength and conformability. The inventors of the present invention have found that introducing a mass ratio of terminal mercapto-butadiene nitrile rubber and epoxy resin into the acrylate copolymer of the adhesive layer can make the tape containing the composite substrate of the present invention have both high strength and high toughness, which is beneficial to improving the conformability of the tape product.
[0121] It can be seen from the test results of Example 4 that if the mass ratio of epoxy resin to mercapto-terminated nitrile rubber exceeds the specified range, the impact performance will decrease.
[0122] It can be seen from the test results of Example 5 that if the ratio of solid epoxy resin to liquid epoxy resin exceeds the specified range, the shear strength of the tape will be affected; if it only contains solid or liquid epoxy resin, its peel force, shear strength or impact strength will not meet the product requirements.
[0123] The test results of Example 6 show that the adhesive tape of the structure of the present invention has higher peeling force, higher shear strength and impact strength.
[0124] The tape sample is directly bonded to a curved test plate (a steel plate with an epoxy coating on the surface) at room temperature to test the tape's conformability. Figure 1 This is a test diagram of the adhesive tape adhesion of Example 6a of the present invention. The adhesive tape is well bonded to the curved test plate without bubbles or bounces. This is a normal qualified product. Figure 2 This is a test diagram of the adhesive tape adhesion of Example 6c of the present invention. At this time, the adhesive tape and the curved test plate are partially bounced up, and there are bubbles and gaps between the adhesive surfaces, indicating poor adhesion. Figure 3 This is a test diagram of the adhesive tape adhesion of Example 6d of the present invention. The adhesive tape and the curved panel cannot be bonded normally, and the curved part directly bounces up, and the adhesion is very poor.
[0125] The test results of the comparative group show that if the present invention does not contain terminal mercapto-butadiene nitrile rubber, its impact strength does not meet the requirements; if terminal hydroxyl-butadiene nitrile rubber is used instead, although it can also have a toughening effect, its shear strength does not meet the product requirements.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. High-strength UV tape, characterized by: It comprises a composite substrate layer and an adhesive layer disposed on at least one side of the composite substrate layer, wherein the composite substrate layer comprises a first substrate layer, an adhesive layer and a second substrate layer in sequence, and the adhesive layer is disposed on the first substrate layer and / or the second substrate layer away from the adhesive layer; The adhesive layer comprises the following components in parts by weight:
2. The high-strength UV tape according to claim 1, characterized in that: The mass ratio of the first epoxy resin to the mercapto-terminated nitrile rubber is (3-20):
1.
3. The high-strength UV tape according to claim 1 or 2, characterized in that: The first epoxy resin comprises a combination of a solid epoxy resin having an epoxy equivalent of 420 to 800 g / eq and a liquid epoxy resin having an epoxy equivalent of 180 to 250 g / eq.
4. The high-strength UV tape according to claim 3, characterized in that: The mass ratio of the solid epoxy resin to the liquid epoxy resin is (1-5):
1.
5. The high-strength UV tape according to claim 1, characterized in that: The first substrate layer and the second substrate layer are both PET films; Preferably, the thickness of the first substrate layer and the second substrate layer are both ≤38 μm; Preferably, the thickness of the first substrate layer and the second substrate layer are each independently selected from 25 to 38 μm.
6. The high-strength UV tape according to claim 1, characterized in that: The thickness of the adhesive layer is 50 to 150 μm.
7. The high-strength UV tape according to claim 1, characterized in that: Adhesive layers are arranged on both sides of the composite substrate layer.
8. The high-strength UV tape according to claim 7, characterized in that: The thickness of the adhesive layer is 50 to 150 μm.
9. A method for preparing the high-strength UV tape according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing and stirring the components of the adhesive layer evenly, coating the components on the surface of the first substrate layer, and then laminating the second substrate layer to perform curing and drying to obtain a composite substrate layer; coating the adhesive of the adhesive layer on at least one side of the composite substrate layer, and obtaining the adhesive layer after curing and drying.
10. The preparation method according to claim 9, characterized in that: The method further comprises the following step: laminating a release film on the surface of the dried adhesive layer.